2016
DOI: 10.1177/1359105315600240
|View full text |Cite
|
Sign up to set email alerts
|

Eating tasty foods to cope, enhance reward, socialize or conform: What other psychological characteristics describe each of these motives?

Abstract: Psychological characteristics associated with eating motives of the Palatable Eating Motives Scale (PEMS) were identified in 192 undergraduates. Coping was characterized by greater BMI, emotion-triggered eating, and eating concern and also by binge-eating and perceived stress reactivity in females. Reward Enhancement was characterized by greater BMI, anxiety- and depression-eating in females and by anger/frustration-eating in males. Conformity was strongly characterized by binge-eating and by failure-based str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 28 publications
4
20
0
Order By: Relevance
“…These results are in line with previous studies, where it was also found that eating driven by emotional reasons is more common among those who already suffered from an eating disorder (Boggiano et al, 2017).…”
supporting
confidence: 93%
“…These results are in line with previous studies, where it was also found that eating driven by emotional reasons is more common among those who already suffered from an eating disorder (Boggiano et al, 2017).…”
supporting
confidence: 93%
“…The safety and tolerability of tDCS in children and adolescents has been proven (Antal et al, 2017 ) so, in a single-blind-controlled study, we hypothesized that excitatory tDCS over the left DLPFC and inhibitory tDCS over the right DLPFC (anode left/cathode right) may aid in altering/resetting inter-hemispheric balance in adolescents with AN, re-establish their control over eating behaviors. This montage was based on the dominance hypothesis in AN and in accordance with previous studies, where opposite stimulation montage showed an improvement in “over-eating” for ED symptoms (Fregni et al, 2008 ; Goldman et al, 2011 ; Montenegro et al, 2012 ; Boggiano et al, 2017 ).…”
Section: Introductionsupporting
confidence: 71%
“…Conversely, tDCS research has mostly focused on food cravings (Fregni et al, 2008 ; Goldman et al, 2011 ; Montenegro et al, 2012 ; Boggiano et al, 2017 ) and evidences have been provided that food cravings is reduced when excitatory (anodal) tDCS is applied over the right DLPFC (as opposite to reports on AN where excitatory stimulation is applied over the left DLPFC). For example, Fregni et al ( 2008 ) compared both tDCS protocols, anode right/cathode left and anode left/cathode right, to sham stimulation, and found that food cravings reduced, remained stable or increased in these conditions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation for these differences between the BE-like profiles is a possible high hedonic threshold or heightened reward sensitivity in binge eaters (Boggiano et al, 2007). Differences in sympathetic reactivity may predispose binge eaters to turn to palatable food while dealing with stress (Boggiano et al, 2007, 2015; Corwin et al, 2011; Burgess et al, 2014; Pool et al, 2015). Stress elevates corticosterone (CORT) that enhances dopamine release in the NAc that affect the motivation toward PF.…”
Section: Discussionmentioning
confidence: 99%
“…Binging usually includes highly palatable foods that are typically characterized by high calorie density and low nutritional values (Oswald et al, 2011; Bekker et al, 2014; Boggiano et al, 2014; Pool et al, 2015) and it is often accompanied by a sense of loss of control in humans (Finlayson et al, 2011; APA, 2013; Boggiano et al, 2014, 2015; Dalton and Finlayson, 2014; Pool et al, 2015) which is triggered by emotional stressors (Boggiano et al, 2007, 2014, 2015; Bello et al, 2014; Pool et al, 2015). Food consumption while binging is not necessarily driven by hunger and therefore it increases various health risks (Finlayson et al, 2011; APA, 2013; Bekker et al, 2014; Boggiano et al, 2015; Imperatori et al, 2015; Pool et al, 2015). Behavioral, emotional, and cognitive properties of BE are seen in 10–20% of the general population (Dalton and Finlayson, 2014).…”
Section: Introductionmentioning
confidence: 99%